Model Kepemtensi Tenaga Administrasi Sekolah Menengah Kejuruan - Lantip Diat Prasojo (Fakultas Ilmu Pendidikan UNY, 2008)
Vocational High School Administrative Personnel Profession enough having immeasurable and requires expertise area and different education' ladder also